Association between the Use of Pessary and the Length Use of Pessary with the Incident of Bacterial Vaginosis on Pelvic Organ Prolapse Patients (Indian Journal of Public Health Research & Development, 2020)
Introduction and Hypothesis: Pelvic Organ Prolapse (POP) is a condition with specific signs such asdescent of the fornix anterior, fornix posterior, uterine, cervix, apex of the vagina after hysterectomy orperineal. The use of pessary is a conservative and the first line of POP medication. Most women who usedpessaries complained about vaginal discharge, more than 50% of them were proven suffered from bacterialvaginosis. This research was aimed to know whether there was any association between the incident of BVwith the use of pessaries and the length use of pessaries among POP patients. We hypothesized that the useof pessaries and the length use of pessaries had a significant association with the incident of BV. This studywas a case-control study. There were 68 medical records, which were obtained through purposive sampling.Independent variables were the use of pessaries and the length use of pessaries, the dependent variable wasthe incident of BV among POP patients. Data collection sheets were the instrument of this research. ChiSquare, Fisher Exact Test and Odd ratio were used to analyze the data. This research used ?: 5%, CI: 95%Result: This research revealed that there was a significant association between the incident of BV on POPpatients with the using of pessaries (P=0.001) and the length use of pessaries (P=0.024). Odd ratio 5.9 (95%CI, 1.95-17.97) means patients with POP who used pessaries had a probability to suffer BV 5.9 times higherthan those who didn’t. Conclusion: there was a significant association between the incident of BV with theuse of pessaries and the length use of pessaries on POP patients.
Keywords: bacterial vaginosis, pelvic organ prolapse, pessary, the length used, the usage